1955
DOI: 10.1172/jci103183
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of I131 Labeled Human Serum Albumin Following Intravenous Administration

Abstract: Previous studies utilizing I'sl' labeled human serum albumin have revealed that approximately 60 per cent of the total exchangeable albumin of nonedematous subjects is in extravascular locations (1,2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1957
1957
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 10 publications
3
42
0
Order By: Relevance
“…Once in the circulating blood, albumin is transported across the capillary wall to the interstitial fluid and body cavity fluids. It is probable that the transport of albumin from the interstitial fluid to plasma is almost exclusively via lymphatics rather than by re-entry of blood capillaries (12 (14). Utilizing the fluorescent antibody technique, Gitlin, Landing and Whipple (15) have demonstrated homologous serum albumin intracellularly in a variety of human tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the circulating blood, albumin is transported across the capillary wall to the interstitial fluid and body cavity fluids. It is probable that the transport of albumin from the interstitial fluid to plasma is almost exclusively via lymphatics rather than by re-entry of blood capillaries (12 (14). Utilizing the fluorescent antibody technique, Gitlin, Landing and Whipple (15) have demonstrated homologous serum albumin intracellularly in a variety of human tissues.…”
Section: Discussionmentioning
confidence: 99%
“…One of the highest extravascular-intravascular ratios ever observed in this laboratory was in a patient with myxedema, in whom 73 per cent of the iodinated albumin remaining within the body at distribution equilibrium was in the extravascular spaces (2). The high extravascular albumin content in myxedema may be related to increased skin thickness since it has been shown that skin contains a disproportionately large fraction of the total extravascular albumin (3). It therefore seemed of interest to evaluate whether extravascular-intravascular shifts of serum albumin could be initiated in euthyroid subjects by the administration of large doses of thyroid hormone.…”
mentioning
confidence: 87%
“…injection the brain RISA curve was practically parallel to the plasma curve; the muscle RISA concentration continued to increase during the 24hr. Rothschild, Bauman, Yalow & Berson (1955) studied the RISA levels in muscle for 22 days after i.v. injection and found that the muscle activity increased steadily during the first 5 days and then remained constant.…”
Section: Sucrosementioning
confidence: 99%